Robert R. Edwards, Invention and Authorship in Medieval England (Ohio State University Press, 2017) (Authorship, 2018)
Robert R. Edwards, Invention and Authorship in Medieval England, Ohio State University Press, Columbus, 2017, 280 pp. $105.95.